AGAMA DAN PENCERAHAN BUDAYA : INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA BUDAYA MASYARAKAT INDONESIA - Sazali Sazali (Universitas Nasional, 2016)
Islam in the realm of culture has shown its unique dynamics. Besides being a cultural force, Islam, for example, has emerged as a resistance movement faced colonialism. In Indonesia, although Islam has become the